Strategy as Practice—Multilevel Institutional Work to Induce Change in Higher Education - Stenvall-Virtanen, Sari (John Wiley & Sons Ltd, 2025)
The characteristics of institutional work in higher education change is an understudied topic in research. This article describes an institutional change process in higher education by analysing multilevel institutional work. Drawing on the results, the paper presents a modified process model on the multilevel institutional work and the related micro–macro linkages. The model describes how micro-level strategy work connects with organisational strategy, the macro-level development and policy. Based on the results, the institutional change in higher education is characterised by the interplay between practice work and boundary work in a process, which has special characteristics at different stages. The empirical focus of the study is in the engineering and technology education in Finland. Using a theory-informed, mixed-methods single-case study design, this study explores the characteristics of multilevel institutional work and transformation mechanisms. The results generate theoretical knowledge on the micro–macro linkages of the institutional change process in higher education.